1990
DOI: 10.1002/1097-0142(19900501)65:9<1907::aid-cncr2820650906>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival rate in primary intracranial lymphoma treated by high-dose radiation and systemic vincristine-doxorubicin-cyclophosphamide-prednisolone chemotherapy

Abstract: Thirty patients with histologically proven primary intracranial non‐Hodgkin's lymphoma were treated at Kyoto University. Ten of them were treated prospectively with a radiation‐chemotherapy protocol. All but four specimens were recently reexamined and classified according to the Working Formulation system. The predominant histologic types were diffuse large cell type, large cell immunoblastic type, and diffuse mixed small and large cell type, seen in 38%, 21%, and 21% of cases, respectively. Before 1980, 16 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It could be valuable to study radiotherapy protocols giving a high dose (> 50 Gy) to the tumour bed and a reduced dose to the whole brain in risk groups 2 and 3. The association of chemotherapy and radiotherapy after surgery has been reported to yield better results than radiotherapy alone (Pollack et al, 1989;Michalski et al, 1990;Shibamato et al, 1989) although this has not consistently been found (Murray et al, 1986). An important point is whether a reduction of chemotherapy intensity in patients over 60 years may be responsible for the worse survival in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be valuable to study radiotherapy protocols giving a high dose (> 50 Gy) to the tumour bed and a reduced dose to the whole brain in risk groups 2 and 3. The association of chemotherapy and radiotherapy after surgery has been reported to yield better results than radiotherapy alone (Pollack et al, 1989;Michalski et al, 1990;Shibamato et al, 1989) although this has not consistently been found (Murray et al, 1986). An important point is whether a reduction of chemotherapy intensity in patients over 60 years may be responsible for the worse survival in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Among therapeutic features, the dose of radiation (Murray et al, 1986;Berry & Simpson, 1981;Pollack et al, 1989;Brada et al, 1990) and treatment with chemotherapy (Pollack et al, 1989;Michalski et al, 1990;Shibamato et al, 1989) The three remaining patients were treated with radiotherapy only because of patient refusal. Relapses were evidenced by CT scan in 20 patients.…”
mentioning
confidence: 99%
“…Complete data of disease-free survival (DFS), overall survival (OS) and management of recurrent or progressive disease after first-line treatment were available for each patient in 24 out of 59 considered series (Sagerman et al, 1967;Rampen et al, 1980;Letendre et al, 1982;Gonzalez and Schuster-Uitterhoeve, 1983;Mendenhall et al, 1983;Loeffler et al, 1985;Woodman et al, 1985;Di Marco et al, 1986;Murray et al, 1986;Vakili et al, 1986;Yasunaga et al, 1986;McLaughlin et al, 1988;Shibamoto et al, 1990;Uematsu et al, 1992;Watne et al, 1992;Boiardi et al, 1993;Glass et al, 1994Glass et al, , 1996Lachance et al, 1994;Ling et al, 1994;Selch et al, 1994;Ferreri et al, 1995b;Sarazin et al, 1995;Freilich et al, 1996). Three hundred and fiftyfive cases were reported in the analysed series: 334 patients received RT, CHT or CTM as first-line treatment, whereas 21 patients were not submitted to any therapy after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…A number of chemotherapeutic regimens have been evaluated in the treatment of immunocompetent patients with primary CNS lymphoma both in the adjuvant and recurrent setting [1,[3][4][5][6][12][13][14][15][16][17]. Given the large number of drugs active against extraneural non-Hodgkins lymphoma, it is not surprising to find a variety of drugs employed against primary CNS lymphoma.…”
Section: Personality and Psychiatric Manifestations; 3) Focal Neurolomentioning
confidence: 99%